Activation of Homolytic SiZn and SiHg Bond Cleavage, Mediated by a Pt0 Complex, via Novel PtZn and PtHg Compounds. Issue 40 (18th August 2015) - Kratish, Yosi; Molev, Gregory; Kostenko, Arseni; Sheberla, Dennis; Tumanskii, Boris; Botoshansky, Mark; Shimada, Shigeru; Bravo‐Zhivotovskii, Dmitry; Apeloig, Yitzhak
Abstract The thermally stable [(tBuMe2Si)2M] (M=Zn, Hg) generate R3Si. radicals in the presence of [(dmpe)Pt(PEt3)2] at 60–80 °C. The reaction proceeds via hexacoordinate Pt complexes, (M=Zn (2 a and 2 b), M=Hg (3 a and 3 b)) which were isolated and characterized. Mild warming or photolysis of 2 or 3 lead to homolytic dissociation of the PtMSiR3 bond generating silyl radicals and novel unstable pentacoordinate platinum paramagnetic complexes (M=Zn (5), Hg (6)) whose structures were determined by EPR spectroscopy and DFT calculations.